2022
DOI: 10.1111/1751-7915.14182
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota, a key to understanding the health implications of micro(nano)plastics and their biodegradation

Abstract: The effects of plastic debris on the environment and plant, animal, and human health are a global challenge, with micro(nano)plastics (MNPs) being the main focus. MNPs are found so often in the food chain that they are provoking an increase in human intake. They have been detected in most categories of consumed foods, drinking water, and even human feces. Therefore, oral ingestion becomes the main source of exposure to MNPs, and the gastrointestinal tract, primarily the gut, constantly interacts with these sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 174 publications
0
10
0
Order By: Relevance
“…Thus, MPs work like a Trojan horse, bringing with them a series of environmental contaminants that can interact with the mucus that lines the GIT, with epithelial cells, and with the intestinal microbiota, causing cellular responses and various physiological changes. 76,77 MP ingestion acts on the gut microbiome and is associated with dysbiosis, loss of resilience, frequent pathogen outbreaks, and local and systemic metabolic disturbances, 78 in addition to the development of an intestinal microbiota that is positively associated with diseases of the digestive tract, such as Bifidobacterium, Streptococcus, and Sphingomonas, and a decline in the intestinal microbiota beneficial to health (Ruminococcus, Fusobacterium, Coprococcus). 76 Chemical contaminants can be transferred from mother to child through breastfeeding, depending on its duration, and the child's body burden generally reflects the burden of maternal exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MPs work like a Trojan horse, bringing with them a series of environmental contaminants that can interact with the mucus that lines the GIT, with epithelial cells, and with the intestinal microbiota, causing cellular responses and various physiological changes. 76,77 MP ingestion acts on the gut microbiome and is associated with dysbiosis, loss of resilience, frequent pathogen outbreaks, and local and systemic metabolic disturbances, 78 in addition to the development of an intestinal microbiota that is positively associated with diseases of the digestive tract, such as Bifidobacterium, Streptococcus, and Sphingomonas, and a decline in the intestinal microbiota beneficial to health (Ruminococcus, Fusobacterium, Coprococcus). 76 Chemical contaminants can be transferred from mother to child through breastfeeding, depending on its duration, and the child's body burden generally reflects the burden of maternal exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Present studies mainly focus on the transformations of MNPs within the respiratory and digestive systems, including their degradation, the release of toxic chemicals, and interactions with other pollutants. MNP degradation in organisms is mainly induced by the gut microflora, reactive oxygen species (ROS), and enzymes, resulting in depolymerization . While gut microflora effectively promote MNP degradation in organisms, current data are limited to insect models .…”
Section: Fates Of Mnps In the Human Bodymentioning
confidence: 99%
“…MNP degradation in organisms is mainly induced by the gut microflora, reactive oxygen species (ROS), and enzymes, resulting in depolymerization. 123 While gut microflora effectively promote MNP degradation in organisms, current data are limited to insect models. 124 Studies have shown that mealworm larvae degrade commonly used plastics such as PS, PP, PE, poly(vinyl chloride) (PVC), and polylactic acid (PLA).…”
Section: Transformation Of Mnps In the Human Bodymentioning
confidence: 99%
“…Other metabolic disorders recorded after exposure to MNPs are associated with alterations of the intestinal microbiota (Jiménez-Arroyo et al, 2023). It is well known that the loss of diversity of the intestine microbiota, known as intestinal dysbiosis, is related to local effects (digestive) as well as systemic (in other organs and tissues), due to the alteration of physiological homoeostasis, causing metabolic diseases.…”
Section: Scientific Evidencementioning
confidence: 99%